1981
DOI: 10.1002/zaac.19814821117
|View full text |Cite
|
Sign up to set email alerts
|

Über die Ordnung von BIII und MV in Perowskiten vom Typ ABIIIMVO6 (AII  Ba, Sr; MV  Sb, Nb, Ta)

Abstract: Die Perowskite Ba2BIIISbO6 kristallisieren monoklin (BIII  La, Pr, Nd) bzw. kubisch (BIII  Sm, Eu, Gd, Tb, Dy, Yb, Lu, Y). Die Sr‐Verbindungen, Sr2BIIISbO6, besitzen eine monokline (BIII  Nd, Sm, Eu, Dy), rhombische (BIII  Yb, Lu, Y, Sc) bzw. kubische (BIII  In, Ga) Perowskitstruktur. Mit Intensitätsberechnungen und schwingungsspektroskopischen Methoden ließen sich Abweichungen von einer vollständigen Ordnung der BIII‐ und SbV‐Ionen nachweisen. In den Perowskiten Ba2BIIIMVO6 mit MV  Nb, Ta ist ebenfalls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
1
17
2
Order By: Relevance
“…To the best of our knowledge, this is the first time that the room-temperature structures of Sr 2 ScSbO 6 and Ca 2 ScSbO 6 are reported. Syntheses of Sr 2 ScSbO 6 have been reported on two occasions [7,17]; however, no structural determination was reported and no space group was identified. In the first study, Sr 2 ScSbO 6 was reported as orthorhombic with unit cell parameters a¼5.678Å; b¼5.691Å; c¼8.021Å [17].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…To the best of our knowledge, this is the first time that the room-temperature structures of Sr 2 ScSbO 6 and Ca 2 ScSbO 6 are reported. Syntheses of Sr 2 ScSbO 6 have been reported on two occasions [7,17]; however, no structural determination was reported and no space group was identified. In the first study, Sr 2 ScSbO 6 was reported as orthorhombic with unit cell parameters a¼5.678Å; b¼5.691Å; c¼8.021Å [17].…”
Section: Introductionmentioning
confidence: 93%
“…Syntheses of Sr 2 ScSbO 6 have been reported on two occasions [7,17]; however, no structural determination was reported and no space group was identified. In the first study, Sr 2 ScSbO 6 was reported as orthorhombic with unit cell parameters a¼5.678Å; b¼5.691Å; c¼8.021Å [17]. The second work reported Sr 2 ScSbO 6 as tetragonal, with a¼8.019Å; c¼8.063Å [7].…”
Section: Introductionmentioning
confidence: 93%
“…Previous reports using conventional (laboratory) X-ray powder diffraction have indicated that the structures of the largest lanthanides (La 3+ -Nd 3+ ) are monoclinic, with smaller lanthanides (Eu 3+ -Tb 3+ ) adopting a tetragonal structure and the smallest lanthanides having cubic symmetry (Dy 3+ -Lu 3+ and Y 3+ ) [4][5][6][7]. However none of these studies determined the complete structures of these perovskites.…”
Section: Introductionmentioning
confidence: 98%
“…Nb, Ta). [ see for example [1][2][3][4][5][6][7][8][9][10][11][12][13][14] A related structure to that of perovskite is the K 2 NiF 4 structure in which perovskite-type layers are separated by rock salt layers (figure 1). A wide range of materials with this structure-type have been prepared and studied including the well-known La 2 CuO 4 based superconductor La 2-x Ba x CuO 4 [15][16][17].…”
Section: Introductionmentioning
confidence: 99%